2009
DOI: 10.1002/app.30525
|View full text |Cite
|
Sign up to set email alerts
|

Role of amphiphilic dopants on the shape and properties of electrically conducting polyaniline‐clay nanocomposite

Abstract: The role of functionality and rigidity of the amphiphilic dopants on the morphology and electrical property of the polyaniline-clay nanocomposites (PANICNs) were studied by preparing polyaniline (PANI) and PANICNs using five structurally different amphiphilic dopants having backbone-phenyl, naphthyl, alicyclic, and alkyl groups. Effect of the size and functionality of the dopant on the extent of intercalation/exfoliation, morphology, thermal stability, and phase transitions were studied. PANICNs exhibited diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Fresh sample solutions were used for each experiment. 3‐PDPSA and PIC were prepared as reported elsewhere …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fresh sample solutions were used for each experiment. 3‐PDPSA and PIC were prepared as reported elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…Block copolymers and surfactants have been reported as stabilizing agents for controlling the size and shape of nanoparticles by capping mechanism . We also observed the formation of nanostructured/microstructured PANI and PANI–clay nanocomposites with amphiphilic dopants developed from cashew nut shell liquid, which played the multiple roles of micellar template, structure‐directing agent, dopant, intercalating agent, and more . Earlier, our group prepared a polyaniline–Keggin iron–clay (PPICS) composite using 3‐pentadecyl phenol‐4‐sulfonic acid (3‐PDPSA) as an amphiphilic dopant and blended it with polycarbonate for electromagnetic interference shielding applications .…”
Section: Introductionmentioning
confidence: 99%
“…For example, strong inorganic hydrochloric acid (HCl), organic and aromatic acids containing different aromatic substitution, such as ptoluene sulphonic acid (PTSA), dodecylbenzenesulphonic acid (DBSA), organic and aliphatic acids having a long hydrocarbon chain, such as lauric acid (LA) and amphiphilic dopants that belong to the family of sulphonic acids have been used as dopants for PANI. The properties of doped conductive polymers depend on the type and molecular size of the dopant (Sinha et al, 2009;Reena et al, 2009). Liu et al (1994) showed that the surface energies of the doped conducting polymers vary greatly, depending on the choice of the dopants and doping level.…”
Section: Conducting Polymersmentioning
confidence: 99%
“…In both PPC and PPTC, the third band is red shifted to 809 nm and 812 nm, respectively due to the presence of delocalized polarons arising from the confined environment of nanoclay layers. 37 Here, the nanoclay layers not only eliminate the interaction of different PANI chains, but also limit the contraction of the chains. Thus in PPTC, PANI is in a more expanded conformation 38 and there is strong interaction between PANI chains and PHT nanoparticles.…”
Section: Uv-visible Spectroscopymentioning
confidence: 99%